Effects of the cell type-specific ablation of the cAMP-responsive transcription factor in noradrenergic neurons on locus coeruleus firing and withdrawal behavior after chronic exposure to morphine - Parlato, Rosanna; Cruz, Hans; Otto, Christiane; Murtra, Patricia; Rodriguez-Parkitna, Jan; Martin, Miquel; Bura, Simona A.; Begus-Nahrmann, Yvonne; Von Bohlen und Halbach, Oliver; Maldonado, Rafael; Schütz, Günther; Lüscher, Christian (Journal of neurochemistry, 2010)
J. Neurochem. (2010) 115, 563-573. Abstract Repeated exposure to opiates leads to cellular and molecular changes and behavioral alterations reflecting a state of dependence. In noradrenergic neurons, cyclic AMP (cAMP)-dependent pathways are activated during opiate withdrawal, but their contribution to the activity of locus coeruleus noradrenergic neurons and behavioral manifestations remains controversial. Here, we test whether the cAMP-dependent transcription factors cAMP responsive element binding protein (CREB) and cAMP-responsive element modulator (CREM) in noradrenergic neurons control the cellular markers and the physical signs of morphine withdrawal in mice. Using the Cre/loxP system we ablated the Creb1 gene in noradrenergic neurons. To avoid adaptive effects because of compensatory up-regulation of CREM, we crossed the conditional Creb1 mutant mice with a Crem−/− line. We found that the enhanced expression of tyrosine hydroxylase normally observed during withdrawal was attenuated in CREB/CREM mutants. Moreover, the withdrawal-associated cellular hyperactivity and c-fos expression was blunted. In contrast, naloxone-precipitated withdrawal signs, such as jumping, paw tremor, tremor and mastication were preserved. We conclude by a specific genetic approach that the withdrawal-associated hyperexcitability of noradrenergic neurons depends on CREB/CREM activity in these neurons, but does not mediate several behavioral signs of morphine withdrawal.
Gesehen am 26.06.2023